Circular Economy: Recent Technology Management Considerations : Supply chain innovation key to business-to-consumer closed-loop systems. Issue 1 (1st January 2020) - Hazen, Benjamin T.; Russo, Ivan; Confente, Ilenia
As citizens, organisations and governments across the globe increase their interest in environmentally and socially sustainable means of production and consumption, the idea of a circular economy (CE) has been at the forefront of recent discussions held at organisational, national and international levels. This article briefly presents the CE concept from a supply chain management perspective. Then, two contemporary, representative CE technology management problems are introduced. The article concludes with some takeaways that policy makers and managers can use to inform further CE development.